Pengaruh Pandemi Covid-19 Terhadap Non Performing Loan Dan Profitabilitas Bank - Rama Nugraha Irawan Surayuda (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This research purposes is to determine Influence of covid-19 pandemic to Non Performing Loan and Bank’s Profitability. Case study of this research was conduct at 15th bank in Indonesia, which is its data research quarterly financial statement from 2018 until 2021. To solve the problem used multiple linear regression using spss ver, 25.0 for Windows. The Research result are Covid-19 pandemic influented to Non Performing Loan Bank, and Covid-19 Pandemic influented to Bank’s Profitability. The result test are viewing negatif influence of Covid-19 Pandemic to non performing loan and bank’s profitability, whitch are not good for condition of health and performance banks.